Faktor Faktor yang Berhubungan dengan Kejadian Stunting pada Balita di Desa Jurusen Kecamatan Pegasing Kabupaten Aceh Tengah Provinsi Aceh Tahun 2022 - Yuliana Yuliana; Kamelia Sinaga; Imran Saputra Surbakti; Asnita Sinaga; Aisa Aulia (Inovasi Kesehatan Global, 2024)
Stunting is a condition of chronic malnutrition characterized by stunted growth in height for a long period of time, so that children have a height that is not appropriate for their age. The purpose of this study is to determine the factors associated with the incidence of stunting in toddlers in Jurusen Village, Pegasing District, Central Aceh Regency in 2022. The method in this study is an analytical observational research type with a research design using a Cross Sectional approach. This research was conducted in Factors Related to the Incidence of Stunting in Toddlers in Jurusen Village, Pegasing District, Central Aceh Regency in 2022. The population in this study was 38 toddlers. then the sample is part of all the objects studied and is considered to represent the entire population. The number of samples used was 38 people using the Total Sampling technique. The data collection technique used a questionnaire sheet and a respondent observation sheet. The data analysis technique used the chi-square statistical test. Based on the results of the statistical analysis, it is known that there is a significant relationship between Exclusive Breastfeeding, Father and Mother's Height, Nutritional Status During Pregnancy, Education Status and Knowledge, on the Incidence of Stunting with a value of p = 0.002 (p <0.05) and the highest Exp (B) value of 11.333. This independent variable dominates the significant influence on the Incidence of Stunting in Toddlers in Jurusen Village, Pegasing District, Central Aceh Regency in 2022.